Pengembangan Media Pembelajaran pada Website Tanpa Jaringan untuk Kemandirian belajar Peserta Didik - Azwal, Rahmi Aulia; Sari, Milya (Natural Science: Jurnal Penelitian Bidang IPA dan Pendidikan IPA, 2019)
The purpose of this study is to design learning media in the form of websites without networks to help students learn independently in material momentum and impulses that are valid, practical and effective. Research is R & D research. This stage of development and development uses the Borg and Gall model which consists of 10 steps. The results showed that the website without the network developed had met the criteria for learning media that were valid, practical and effective. The results of the expert validation show that websites without networks are very valid from the aspects of content, construction and language. The results of the trial to see the practicality of showing a website without a network can be used in learning and is easy to use by teachers and students. The effectiveness of a website without a network that is seen from learning independence shows that students are very helpful for independent learning at home, because it is easy to use, the material is easy to understand and fits the needs of students.